2018
DOI: 10.1017/s1092852918001311
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of prediabetes and metabolic abnormalities in overweight or obese schizophrenia patients treated with clozapine or olanzapine

Abstract: ObjectiveTo assess the prevalence of prediabetes and metabolic abnormalities among overweight or obese clozapine- or olanzapine-treated schizophrenia patients, and to identify characteristics of the schizophrenia group with prediabetes.MethodsA cross-sectional study assessing the presence of prediabetes and metabolic abnormalities in schizophrenia clozapine- or olanzapine-treated patients with a body mass index (BMI) ≥27 kg/m2. Procedures were part of the screening process for a randomized, placebo-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 56 publications
2
20
1
Order By: Relevance
“…In this study, disease-related characteristics did not show statistically significant differences in the presence or absence of metabolic syndrome. These results differ from previous studies that reported that schizophrenia patients with metabolic syndrome had a longer prevalence than schizophrenia patients without metabolic syndrome and that olanzapine and clozapine were the major risk factors for developing metabolic syndrome [ 7 , 10 , 11 ]. This discrepancy may have occurred due to the fact that in this study, medications and dosage were only checked at the time of research, and it was difficult to verify the exact duration and dosage of medications that participants were taking at the community mental health care centers where data collection was conducted.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this study, disease-related characteristics did not show statistically significant differences in the presence or absence of metabolic syndrome. These results differ from previous studies that reported that schizophrenia patients with metabolic syndrome had a longer prevalence than schizophrenia patients without metabolic syndrome and that olanzapine and clozapine were the major risk factors for developing metabolic syndrome [ 7 , 10 , 11 ]. This discrepancy may have occurred due to the fact that in this study, medications and dosage were only checked at the time of research, and it was difficult to verify the exact duration and dosage of medications that participants were taking at the community mental health care centers where data collection was conducted.…”
Section: Discussioncontrasting
confidence: 99%
“…Antipsychotics used to alleviate the negative symptoms of schizophrenia have adverse effects, including increased appetite and delayed satiety [ 10 ]. In particular, clozapine and olanzapine cause metabolic disorders such as weight gain, type 2 diabetes, and cardiovascular disease [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent cross-sectional study, prediabetes and metabolic abnormalities were found to be highly prevalent among schizophrenic patients taking clozapine or olanzapine [34]. Interestingly, previous reports have found that patients who are on clozapine or olanzapine are at a high risk of developing hyperlipidemia [35].…”
Section: Discussionmentioning
confidence: 99%
“…The negative effects of smoking on morbidity and premature mortality in individuals with schizophrenia are well established [16,17]. Furthermore, prediabetic conditions and metabolic abnormalities are highly prevalent among patients treated with clozapine [18], and presumably higher dosages of clozapine among smokers might be associated with a higher risk of unfavourable metabolic outcomes due to dose-dependent side effects [19,20].…”
Section: Introductionmentioning
confidence: 99%